Artificial aggregate inner blank and preparation method thereof, artificial aggregate and preparation method and application thereof
By combining dipolymer and mud-based solid waste, silica and calcium oxide are stimulated to form an efficient hydrated gel and wrapping the cement-based encapsulation shell, the problem of natural aggregate mining pressure and solid waste utilization is solved, and artificial aggregates are improved The compressive strength meets construction needs and promotes solid waste reuse.
Patent Information
- Application Number
- CN202411352512.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2024-12-31
AI Technical Summary
In the prior art, excessive exploitation of natural aggregates leads to ecological and environmental problems, industrial solid waste such as ultrafine tailings and petroleum coke slags have not been fully utilized, and the compressive strength of artificial aggregates prepared from sludge-based solid waste is insufficient. Meet construction engineering needs.
Artificial aggregate endomorphs are prepared by using geopolymers (blast furnace slag powder, desulfurized petroleum coke slag and fly ash) and mud-based solid waste (ultrafine tailings, sawn mud and sand washing mud) and stimulated by composite exciters. Silicon oxide and calcium oxide form efficient calcium silicate and calcium aluminate gels that increase the density and compressive strength of the aggregate and wrap the cement-based encapsulation shell to enhance performance.
It has achieved effective replacement of natural aggregates, alleviated the pressure of resource mining, promoted solid waste reuse, improved the compressive strength of artificial aggregates, met the needs of construction projects, and avoided secondary pollution, which has good social benefits.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of recycling, treating and reusing construction waste, and specifically relates to an artificial aggregate endostearum and a preparation method thereof, an artificial aggregate and a preparation method and application thereof. Background Art
[0002] With the rapid development of engineering construction, the use of aggregates has increased day by day, becoming the second largest natural resource consumed by humans. At present, most of the aggregates used are natural aggregates mined from mountains. The huge use of natural aggregates has led to over-exploitation of sand and gravel mine resources, which in turn has caused a series of ecological and environmental problems.
[0003] In addition, ultrafine tailings are a kind of solid waste left after mineral processing in mining projects, which can be used as secondary resources. According to incomplete statistics, the utilization rate of ultrafine tailings is currently increasing year by year, but this value is still far lower than the yield of ultrafine tailings. A large amount of ultrafine tailings waste is not fully utilized. The vast majority of ultrafine tailings accumulation not only occupies a large amount of land resources, but also causes environmental problems, such as harmful dust pollution and air, and the seepage of harmful metal substances pollutes land resources and water resources.
[0004] With the rapid growth of people's demand for industrial products, the petrochemical industry has also developed rapidly. According to the statistics of the General Administration of Customs, the domestic crude oil import volume reached 418 million tons in 2018, and my country's external dependence on crude oil reached 70.9%. The scale of domestic refineries has also continued to increase. Shandong Province has become the world's third largest refining center, with a total refining capacity of 210 million tons. The corresponding output of petroleum coke desulfurization ash is also quite huge. The annual ash discharge in Qingdao alone exceeds 500,000 tons. The main components of ash are CaSO4 and lime, which determines that it has certain gelling properties and can be used in the production of green building materials. The application of desulfurized petroleum coke slag in green building materials is of great significance to the resource utilization of bulk industrial solid waste and the alleviation of resource shortages.
[0005] In addition, granite is formed by the cooling and solidification of magma in the earth's crust, and is mainly composed of mineral phases such as quartz, feldspar and a small amount of mica. my country's granite slab production is about 500 million square meters, and more than 10 million tons of granite sawdust are produced each year. The storage of these wastes not only occupies land, but also causes environmental problems such as dust and soil pollution. Sawdust waste is not fully utilized. The vast majority of sawdust accumulation not only occupies a large amount of land resources, but also causes environmental problems, such as harmful dust pollution and air, and the seepage of harmful metal substances pollutes land resources and water resources.
[0006] At present, people have begun to pay attention to and develop methods for producing artificial aggregates using mud-based solid waste. However, the artificial aggregates currently prepared using mud-based solid waste as the main raw material have poor compressive strength and cannot meet the needs of actual construction projects. Summary of the invention
[0007] The purpose of the present invention is to provide an artificial aggregate endostem and a preparation method thereof, an artificial aggregate and a preparation method and application thereof. The artificial aggregate provided by the present invention can be an effective substitute for natural aggregate, can alleviate the excessive exploitation of natural aggregate, and at the same time realize "waste-to-solid waste", realize the efficient organic combination of energy conservation and emission reduction in the building materials industry, promote the disposal of production waste, and save natural resources; and the artificial aggregate provided by the present invention has excellent compressive strength and can meet the needs of construction projects.
[0008] In order to achieve the above object, the present invention provides the following technical solutions:
[0009] The present invention provides an artificial aggregate endoderm, comprising the following raw materials in percentage by weight:
[0010] Geopolymer 9-40%, mud-based solid waste 45-76%, water 9-20%, water reducer 0.01-6%;
[0011] The geopolymer includes blast furnace slag powder, desulfurized petroleum coke slag and fly ash;
[0012] The mud-based solid waste includes ultrafine tailings, saw mud and sand washing mud.
[0013] Preferably, the mass percentages of blast furnace slag powder, desulfurized petroleum coke slag and fly ash in the artificial aggregate endostear are respectively:
[0014] Blast furnace slag powder 9-20%, desulfurized petroleum coke slag 0.1-10%, fly ash 0.1-10%.
[0015] Preferably, the mass percentages of ultrafine tailings, saw mud and sand washing mud in the artificial aggregate inner embryo are respectively:
[0016] Ultrafine tailings 25-36%, saw mud 10-20%, sand washing mud 10-20%.
[0017] Preferably, the raw materials for preparing the artificial aggregate endostearum further include a composite activator, and the composite activator is a mixed solution of water glass and NaOH;
[0018] The mass of the composite activator is calculated based on the mass of Na2O, and the mass ratio of Na2O in the composite activator to the mass of the geopolymer is (0.03-0.05):1.
[0019] Preferably, the mineral composition of the desulfurized petroleum coke slag includes calcium oxide and calcium sulfate;
[0020] The specific surface area of the blast furnace slag powder is 400-410m 2 / kg, the water hardness coefficient is 1.5-1.74, the alkalinity coefficient is 0.5-0.88, and the activity coefficient is 0.3-0.46.
[0021] Preferably, the density of the artificial aggregate endomorph is 2000-2100 kg / m 3 The water absorption rate is 0.5~1%.
[0022] The present invention provides a method for preparing the artificial aggregate endoderm described in the above technical solution, comprising the following steps:
[0023] mixing geopolymer, mud-based solid waste, water and a water reducing agent to obtain an endomorphic slurry;
[0024] The endoderm slurry is formed and then cured to obtain the artificial aggregate endoderm.
[0025] The present invention provides an artificial aggregate, comprising an artificial aggregate endoderm and a cement-based encapsulation shell wrapped around the surface of the artificial aggregate endoderm; the artificial aggregate endoderm is the artificial aggregate endoderm described in the above technical solution or the artificial aggregate endoderm prepared by the preparation method described in the above technical solution.
[0026] The present invention provides a method for preparing the artificial aggregate described in the above technical solution, comprising the following steps:
[0027] Mixing the raw materials for preparing the cement-based encapsulation shell to obtain a cement-based slurry;
[0028] The artificial aggregate endostearum is immersed in the cement-based slurry for encapsulation to obtain an artificial aggregate semi-finished product;
[0029] The artificial aggregate semi-finished product is cured to obtain the artificial aggregate.
[0030] The present invention provides the use of the artificial aggregate described in the above technical solution or the artificial aggregate prepared by the preparation method described in the above technical solution in building materials.
[0031] The present invention provides a method for preparing the artificial aggregate endoderm described in the above technical solution, comprising the following steps:
[0032] Mixing the raw materials for preparing the cement-based encapsulation shell to obtain a cement-based slurry;
[0033] The artificial aggregate endostearum is immersed in the cement-based slurry for encapsulation to obtain an artificial aggregate semi-finished product;
[0034] The artificial aggregate semi-finished product is cured to obtain the artificial aggregate.
[0035] The present invention provides the use of the artificial aggregate described in the above technical solution or the artificial aggregate prepared by the preparation method described in the above technical solution in building materials.
[0036] The present invention provides an artificial aggregate endomorph, comprising the following raw materials in percentage by weight: 9-40% geopolymer, 45-76% mud-based solid waste, 9-20% water, and 0.01-6% water reducer; the geopolymer comprises blast furnace slag powder, desulfurized petroleum coke slag, and fly ash; the mud-based solid waste comprises ultrafine tailings, saw mud, and sand washing mud. The present invention utilizes geopolymer (blast furnace slag powder, desulfurized petroleum coke slag, and fly ash) and mud-based (ultrafine tailings, saw mud, and sand washing mud) solid wastes as raw materials for preparing artificial aggregate endomorph, and the prepared coarse aggregate product becomes an effective substitute for natural aggregate, which can alleviate the over-exploitation of natural aggregate, and at the same time realizes "waste treatment with waste", and realizes the efficient organic combination of energy conservation and emission reduction in the building materials industry. The artificial aggregate endomorph provided by the present invention will not cause secondary pollution. Geopolymer and mud-based solid waste in production directly become the main components of the artificial aggregate endomorph product, and no secondary pollution is generated. It has good social benefits, promotes the disposal of ultra-fine tailings, saw mud and sand washing mud, saves natural resources, and protects the natural environment. The results of the examples show that the artificial aggregate endomorph provided by the present invention has excellent compressive strength and can meet the needs of construction projects.
[0037] Furthermore, in the present invention, the raw materials for preparing the artificial aggregate endomorph also include a composite activator, which is a mixed solution of water glass and NaOH; the mass of the composite activator is calculated as the mass of Na2O, and the mass ratio of Na2O in the composite activator to the mass of the geopolymer is (0.03-0.05):1. The artificial aggregate endomorph provided by the present invention can effectively activate silicon oxide and calcium oxide in the geopolymer by adding the composite activator to the prepared raw materials, promote the formation of calcium silicate hydrate (CSH) and calcium aluminate hydrate (CAH) gel, make the aggregate endomorph more compact, and obtain an artificial aggregate endomorph product with better compressive strength.
[0038] The present invention provides an artificial aggregate, comprising an artificial aggregate endoderm and a cement-based encapsulation shell wrapped on the surface of the artificial aggregate endoderm; the artificial aggregate endoderm is the artificial aggregate endoderm described in the above technical solution or the artificial aggregate endoderm prepared by the preparation method described in the above technical solution. The cement-based encapsulation shell in the present invention not only strengthens the artificial aggregate endoderm, but also effectively prevents the leakage of harmful substances inside the artificial aggregate endoderm. The endoderm-shell of the artificial aggregate has a good interface transition zone with excellent compressive strength, which can meet the actual engineering needs. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 A schematic diagram of the structure and packaging of the artificial aggregate endometrium and artificial aggregate provided by the present invention;
[0040] Figure 2 A physical picture of the artificial aggregate endometrium prepared by the present invention;
[0041] Figure 3 A physical picture of the artificial aggregate prepared for the present invention;
[0042] Figure 4 is the XRD diffraction pattern of desulfurized petroleum coke slag;
[0043] Figure 5 is the XRD diffraction pattern of blast furnace slag powder;
[0044] Figure 6 is the ternary mix ratio of the geopolymer in the embodiment of the present invention;
[0045] Figure 7 The distribution trend of the ternary contour lines of the 7d compressive strength of the products before optimization of different slurry mix ratios in the embodiments of the present invention;
[0046] Figure 8 The distribution trend of the ternary contour lines of the 7d compressive strength of the products with different optimized slurry mix ratios in the embodiments of the present invention;
[0047] Fig. 9 The distribution trend of the ternary contour lines of the 14d compressive strength of the products with different optimized slurry mix ratios in the embodiments of the present invention;
[0048] Fig.10 The ternary system 7d compressive strength contour diagram is obtained for the products before and after optimization of different slurry mix ratios in the embodiments of the present invention;
[0049] Fig.11 The figure is the test result of the endoderm paste consistency test in the embodiment of the present invention. DETAILED DESCRIPTION
[0050] The present invention provides an artificial aggregate endoderm, comprising the following raw materials in percentage by weight:
[0051] Geopolymer 9-40%, mud-based solid waste 45-76%, water 9-20%, water reducer 0.01-6%;
[0052] The geopolymer includes blast furnace slag powder, desulfurized petroleum coke slag and fly ash;
[0053] The mud-based solid waste includes ultrafine tailings, saw mud and sand washing mud.
[0054] In the present invention, unless otherwise specified, all preparation raw materials / components are commercially available products well known to those skilled in the art.
[0055] In terms of mass percentage, the artificial aggregate endostear provided by the present invention comprises 9-40%, preferably 11-38%, and more preferably 14-35% of geopolymer. In the present invention, the geopolymer preferably comprises blast furnace slag powder (also referred to as mineral powder in the present invention), desulfurized petroleum coke slag (also referred to as petroleum coke slag in the present invention) and fly ash.
[0056] In the present invention, the desulfurized petroleum coke residue is a solid waste obtained by desulfurizing sulfur-containing petroleum coke using a circulating fluidized bed boiler combustion technology. In a specific embodiment of the present invention, the desulfurized petroleum coke residue is produced by Qingdao Petrochemical Refinery. The mineral composition of the desulfurized petroleum coke residue preferably includes calcium oxide and type II anhydrite.
[0057] In a specific embodiment of the present invention, the chemical composition of the desulfurized petroleum coke slag includes: SO3 21.51%, CaO 55.81%, CO2 10.55%, SiO2 2.40%, MgO 2.12%, Al2O3 0.31%, and Fe2O3 0.19%.
[0058] In the present invention, the blast furnace slag powder is granulated blast furnace slag powder (GBFS), and the granulated blast furnace slag powder (GBFS) comes from Qingdao Jimo Plant of China Construction Western Construction. The specific surface area of the blast furnace slag powder is preferably 410m 2 / kg, the water hardness coefficient is preferably 1.74, the alkalinity coefficient is preferably 0.88, and the activity coefficient is preferably 0.46.
[0059] In a specific embodiment of the present invention, the chemical composition of the blast furnace slag powder includes: CaO36.23%, SiO232.35%, Al2O314.87%, MgO 5.18%, TiO20.87%, MnO 0.31%, and Fe2O31.76%.
[0060] In the present invention, the mass percentages of blast furnace slag powder, desulfurized petroleum coke slag and fly ash in the artificial aggregate inner embryo are preferably: blast furnace slag powder 9-20%, desulfurized petroleum coke slag 0.1-10%, fly ash 0.1-10%; more preferably: blast furnace slag powder 11-18%, desulfurized petroleum coke slag 2-8%, fly ash 2-8%; further preferably: blast furnace slag powder 14-15%, desulfurized petroleum coke slag 2-5%, fly ash 2-5%, and most preferably: blast furnace slag powder 14.5-15%, desulfurized petroleum coke slag 4-5%, fly ash 4-5%.
[0061] In terms of mass percentage, the artificial aggregate inner mold provided by the present invention includes 45-76% mud-based solid waste, preferably 47-74%, and more preferably 50-71%. In the present invention, the mud-based solid waste includes ultrafine tailings, saw mud and sand washing mud. The mesh number of the ultrafine tailings is ≤100 mesh, the mesh number of the saw mud is ≤100 mesh, and the mesh number of the sand washing mud is ≤100 mesh. In the present invention, the mass percentages of ultrafine tailings, saw mud and sand washing mud in the artificial aggregate inner mold are preferably: ultrafine tailings 25-36%, saw mud 10-20%, sand washing mud 10-20%; more preferably: ultrafine tailings 27-34%, saw mud 12-18%, sand washing mud 12-18%; more preferably: ultrafine tailings 30-31%, saw mud 15-16%, sand washing mud 15-16%.
[0062] Calculated by mass percentage, the artificial aggregate endostearum provided by the present invention includes 9-20% water, preferably 11-19.5%, and more preferably 14-19.5%.
[0063] In terms of mass percentage, the artificial aggregate endostearum provided by the present invention comprises 0.01-6%, preferably 0.9-4%, and more preferably 0.95-3% of a water reducer. In the present invention, the water reducer is preferably a polycarboxylic acid high-performance water reducer.
[0064] The raw materials for preparing the artificial aggregate endostearum provided by the present invention preferably also include a composite activator, and the composite activator is a mixed solution of water glass and NaOH. The present invention achieves modification of the water glass solution by adding NaOH solid. In the present invention, the modulus of the water glass is preferably 2.4. The modulus of the mixed solution of water glass and NaOH is preferably 2.0. In the present invention, the mass of the composite activator is measured by the mass of Na2O, and the ratio of the mass of Na2O in the composite activator to the mass of the geopolymer is preferably (0.03-0.05):1, and specifically 0.05:1 in the embodiment.
[0065] In the present invention, in order to improve the strength of the artificial aggregate endomorph, a composite activator is added during the preparation of the artificial aggregate endomorph to perform geopolymer activation treatment, thereby improving the compressive strength of the artificial aggregate endomorph and reducing the cost.
[0066] The present invention provides a method for preparing the artificial aggregate endoderm described in the above technical solution, comprising the following steps:
[0067] mixing geopolymer, mud-based solid waste, water and a water reducing agent to obtain an endomorphic slurry;
[0068] The endoderm slurry is formed by an integrated process of extrusion-cutting-polishing and then cured to obtain the artificial aggregate endoderm.
[0069] The present invention mixes geopolymer, mud-based solid waste, water and a water reducing agent to obtain an endomorph slurry. In the present invention, when the raw materials for preparing the artificial aggregate endomorph also include a composite activator, the mixing step is replaced by: mixing geopolymer, mud-based solid waste, water, a composite activator and a water reducing agent to obtain an endomorph slurry.
[0070] In the present invention, before the mixing, the present invention preferably pre-treats the mud-based solid waste. The pre-treatment method of the saw mud or washed sand mud preferably includes: drying, crushing and screening the raw materials of the saw mud or washed sand mud in sequence. The pre-treatment method of the ultrafine tailings preferably includes: drying and screening the raw materials of the ultrafine tailings in sequence. In the present invention, during the pre-treatment process: the drying is preferably oven drying. The present invention has no special requirements for the specific implementation process of the crushing and screening. The mixing preferably includes the following steps: first mixing the geopolymer and the mud-based solid waste to obtain a powder; second mixing the water and the water reducer to obtain a slurry. In the present invention, when the raw materials for preparing the artificial aggregate endoderm also include a composite activator, the first mixing is replaced by: second mixing the water, the water reducer and the composite activator solution to obtain a slurry; and third mixing the powder and the slurry to obtain the endoderm slurry. The first mixing is carried out under stirring conditions, and the first mixing preferably includes: stirring at a low speed for 3 minutes and stirring at a medium speed for 2 minutes, the rotation speed of the low speed stirring is preferably 60±2r / min, and the rotation speed of the medium speed stirring is preferably 80±2r / min. The second mixing is carried out under stirring conditions, and the time of the second mixing is preferably 2min. The third mixing preferably includes: adding the water reducing agent solution to the powder in two times, and the third mixing is carried out under stirring conditions, and the third mixing preferably includes: stirring at a low speed for 3 minutes and stirring at a medium speed for 3 minutes, the rotation speed of the low speed stirring is preferably 60±2r / min, and the rotation speed of the medium speed stirring is preferably 80±2r / min.
[0071] After obtaining the endomorph slurry, the present invention performs curing after molding the endomorph slurry, specifically, the endomorph slurry is molded by an integrated process of extrusion-cutting-polishing and then cured to obtain the artificial aggregate endomorph. In the present invention, the molding is preferably carried out in a double-helix material cutting machine. The present invention has no special requirements for the specific implementation of the molding. The curing is preferably carried out in a standard curing room, and the curing time is preferably 28 days.
[0072] The density of the artificial aggregate endomorph provided by the present invention is 2000-2100 kg / m 3 The water absorption rate is 0.5-1%, and specifically 0.9% in the embodiment.
[0073] The present invention provides an artificial aggregate, comprising an artificial aggregate endoderm and a cement-based encapsulation shell wrapped around the surface of the artificial aggregate endoderm; the artificial aggregate endoderm is the artificial aggregate endoderm described in the above technical solution or the artificial aggregate endoderm prepared by the preparation method described in the above technical solution.
[0074] The artificial aggregate provided by the present invention includes an artificial aggregate endoderm. The artificial aggregate endoderm is the artificial aggregate endoderm described in the above technical solution or the artificial aggregate endoderm prepared by the preparation method described in the above technical solution.
[0075] The artificial aggregate provided by the present invention includes a cement-based encapsulation shell wrapped on the surface of the artificial aggregate inner embryo. In the present invention, the raw materials for preparing the cement-based encapsulation shell (also referred to as UHPC shell in the present invention) preferably include: silica fume, cement, sand, water and water reducer. The water reducer used in the cement-based encapsulation shell is preferably a polycarboxylic acid high-performance water reducer. In a specific embodiment of the present invention, the slurry for preparing the cement-based encapsulation shell is specifically a cement-based encapsulation skin slurry. The cement-based encapsulation skin slurry is specifically an ultra-high performance mortar.
[0076] In the present invention, the mass ratio of the silica fume to the cement is preferably (178-185):880, and more preferably 178:880. The mass ratio of the silica fume to the sand is preferably (178-185):(880-900), and more preferably 178:900. The mass ratio of the silica fume to the water is preferably (178-185):(170-880), and more preferably 178:170. The mass ratio of the silica fume to the water reducer used in the cement-based encapsulation shell is preferably (85-178):(30-35), and more preferably 178:30.
[0077] The present invention provides a method for preparing the artificial aggregate described in the above technical solution, comprising the following steps:
[0078] Mixing the raw materials for preparing the cement-based encapsulation shell to obtain a cement-based slurry;
[0079] The artificial aggregate endostearum is immersed in the cement-based slurry for encapsulation to obtain an artificial aggregate semi-finished product;
[0080] The artificial aggregate semi-finished product is cured to obtain the artificial aggregate.
[0081] The present invention mixes the raw materials for preparing the cement-based encapsulation shell to obtain a cement-based slurry. The mixing preferably includes the following steps: premixing the silica fume, cement, sand and water reducing agent to obtain a premix; and stirring and mixing the premix and water to obtain a cement-based slurry.
[0082] After obtaining the cement-based slurry, the present invention immerses the artificial aggregate endostearth into the cement-based slurry for encapsulation to obtain an artificial aggregate semi-finished product. In the present invention, the encapsulation is performed under stirring conditions.
[0083] After obtaining the semi-finished artificial aggregate, the present invention performs curing on the semi-finished artificial aggregate to obtain the artificial aggregate. The curing is performed in a standard curing room.
[0084] The invention provides a method for preparing artificial aggregate. In the artificial aggregate molding, the invention preferably adopts an integrated extrusion-cutting-polishing process. Compared with the shaking ball granulation, the invention can greatly reduce the pores inside the aggregate endocast, thereby greatly improving the aggregate performance.
[0085] The present invention provides the use of the artificial aggregate described in the above technical solution or the artificial aggregate prepared by the preparation method described in the above technical solution in building materials. The present invention has no special requirements on the specific implementation of the application.
[0086] In order to further illustrate the present invention, the technical solutions provided by the present invention are described in detail below in conjunction with embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0087] Example 1
[0088] In the following embodiment 1: the structure and packaging diagram of the artificial aggregate endomorph and the artificial aggregate are as shown in Figure 1 As shown, the actual picture of the artificial aggregate endoderm prepared in Example 1 is as follows Figure 2 The actual picture of the artificial aggregate prepared in Example 1 is as shown in Figure 3 shown.
[0089] The coarse aggregate (i.e., artificial aggregate) prepared from geopolymer mud-based solid waste provided in Example 1 includes blast furnace slag powder, petroleum coke slag, fly ash, saw mud, sand washing mud, ultrafine tailings, water, water glass solution, NaOH solid and polycarboxylic acid high-performance water reducing agent and other admixtures;
[0090] The method for preparing coarse aggregate (i.e., artificial aggregate) based on alkali-activated geopolymer solid waste provided in Example 1 comprises the following steps:
[0091] S1 Pretreatment of water glass solution (composite activator): According to the modulus required by the experiment, NaOH solid is added to the water glass solution (modulus is 2.4) to adjust the modulus of the water glass solution to obtain a composite activator (modulus is 2.0);
[0092] S2 Mud-based solid waste pretreatment: Drying, crushing and pulverizing of mud-based solid waste. The particle size of ultrafine tailings is relatively uniform, so only drying and screening are required;
[0093] S3 Weighing materials: According to the optimal mix ratio, use an electronic balance to weigh the required activator, blast furnace slag powder, petroleum coke slag, fly ash, saw mud, sand washing mud, and ultra-fine tailings; use a measuring cup to weigh the required water and water reducing agent for later use;
[0094] S4 Powder mixing: Pour all the weighed powders into the mortar mixing pot, stir at low speed for 3 minutes, then switch to medium speed and stir for 2 minutes to ensure that all the powders are fully mixed.
[0095] S5 solution preparation: Pour the water glass solution, water and water reducing agent required for the experiment into a beaker, stir thoroughly with a stirring rod for 2 minutes to make it evenly stirred for later use;
[0096] S6 Endodermal slurry preparation: Pour the reserved solution in S5 into the mortar mixing pot twice, stir at low speed for 3 minutes, then switch to medium speed for 3 minutes;
[0097] S7 Endomorph forming: the slurry prepared in S6 is poured into a double-screw material cutting machine to obtain a number of small cylinders; the small cylinders are then poured into a polishing machine for shape optimization in multiple times, and the final aggregate endomorph is placed in a standard curing room for curing for 28 days;
[0098] S9 Preparation of HPC slurry: Mix the weighed cement and admixtures evenly, add water and stir with a mortar mixer, and put the prepared cement-based slurry into a beaker;
[0099] S10 encapsulated aggregate: put the cured aggregate embryos into the cement-based slurry according to the number, and stir them thoroughly with a glass rod so that the aggregates are fully wrapped by the slurry.
[0100] S11 Curing: Take out the packaged coarse aggregate and place it in the standard curing room for curing.
[0101] In Example 1:
[0102] (1) The desulfurized petroleum coke residue used in this embodiment is a solid waste obtained by desulfurizing sulfur-containing petroleum coke using a circulating fluidized bed boiler combustion technology. The desulfurized petroleum coke residue used in this embodiment is produced by Qingdao Petrochemical Refinery. The XRD diffraction pattern of the desulfurized petroleum coke residue is ( Figure 4 The analysis found that the diffraction peaks of CaSO4 and CaO were relatively obvious, indicating that the main mineral components in the desulfurized petroleum coke slag were calcium oxide and type II anhydrite. The powder was subjected to X-ray fluorescence analysis (XRF) and the results are shown in Table 1. Figure 4 XRD diffraction pattern of petroleum coke residue
[0103] Table 1 Chemical composition of petroleum coke residue (%)
[0104] chemical composition <![CDATA[SO3]]> CaO <![CDATA[CO2]]> <![CDATA[SiO2]]> MgO <![CDATA[Al2O3]]> <![CDATA[Fe2O3]]> Petroleum coke residue 21.51 55.81 10.55 2.40 2.12 0.31 0.19
[0105] The granulated blast furnace slag powder (GBFS) used in this example comes from the Qingdao Jimo Plant of China Construction Western Construction, with a specific surface area of 410m 2 / kg, its main chemical components are shown in Table 2.
[0106] Table 2 Chemical composition of blast furnace slag powder (%)
[0107] chemical composition CaO <![CDATA[SiO2]]> <![CDATA[Al2O3]]> MgO <![CDATA[TiO2]]> MnO <![CDATA[Fe2O3]]> Blast furnace slag powder 36.23 32.35 14.87 5.18 0.87 0.31 1.76
[0108] From Table 2, we can know that the mineral powder:
[0109] Hydraulic coefficient: b = 1.74 > 1.4
[0110] Alkalinity coefficient: M0=0.88<1.0
[0111] Activity coefficient: H0=0.46>0.25
[0112] According to calculations, the mineral powder has a hydraulic hardness coefficient of 1.74, an alkalinity coefficient of 0.88 and an activity coefficient of 0.46. It has high alkalinity and good activity and can be used as geopolymer material.
[0113] XRD diffraction pattern analysis of mineral powder ( Figure 5 ), it can be seen that there is a wide camel-shaped pattern between 25 and 40° in the XRD diffraction spectrum of the mineral powder, and no obvious crystalline phase minerals are found. This shows that the minerals in the mineral powder are mainly glassy phase and have high activity. Figure 5 This is the XRD diffraction pattern of blast furnace slag powder.
[0114] (2) Mixing ratio
[0115] This embodiment takes into account that the irregular shape of the aggregate after forming will cause the measurement results to be highly discrete. In the optimal mix ratio determination stage, the slurry is prepared into 20×20×20mm test blocks and 7d, 14d, and 28d compressive strength tests are performed to determine the optimal mix ratio.
[0116] The present invention realizes sludge solidification by using water glass solution + NaOH composite to excite ternary geopolymer, wherein the alkali equivalent is 0.05; wherein the alkali equivalent refers to the ratio of the mass of Na2O in the water glass solution to the mass of the cementitious material, wherein the cementitious material refers to mineral powder, fly ash, and petroleum coke residue.
[0117] Clean slurry: mud = 1:2. Figure 6 Table 3 is the ternary mix ratio of cementitious materials. Table 4 is the slurry mix ratio.
[0118] Table 3 Pure slurry mix ratio
[0119]
[0120]
[0121] Table 4 Mud mix ratio
[0122]
[0123] Its 7d compressive strength is shown in Table 5 and Figure 7 As shown:
[0124] Table 5 7d compressive strength under the condition of pure slurry mix ratio
[0125]
[0126] According to the distribution trend of the ternary contour line of 7d compressive strength, the mix ratio is further refined for the area above 10MPa and in the lower right corner of the ternary area (such as Figure 8 and Fig. 9 ) to achieve a more accurate gelling mix ratio.
[0127] The improved 7d and 14d compressive strength test results are shown in Table 6.
[0128] Table 6 Compressive strength after improvement
[0129]
[0130]
[0131] The 7d compressive strength before and after improvement is integrated to obtain the 7d compressive strength contour map of the ternary system, as shown in Fig.10 shown.
[0132] The optimal mix ratio obtained from the above is K80-S10-F20, where K is mineral powder, S is petroleum coke slag, and F is fly ash.
[0133] From an economic perspective, the ternary curing agent is determined to be K60-S20-F20.
[0134] On the basis of the above, the amount of water and water reducing agent is regulated and the consistency value is tested (quantitative control, such as Fig.11 The material is in a stable state. The best consistency is 13-15mm. Fig.11 This is a test for the consistency of the endoderm paste.
[0135] Table 7 Extrusion-cutting I endometrium mix ratio
[0136]
[0137] Considering economic factors, the present invention considers the removal of water glass solution, wherein the petroleum coke residue contains more CaO, which provides a sufficient alkaline environment for the reaction. A good extrusion effect is achieved through preliminary tests, and the extrusion-cutting II endoderm mix ratio is used as the final mix ratio of the artificial aggregate endoderm of the present invention. The mix ratio is as follows:
[0138] Table 8 Extrusion-cutting II endometrium mix ratio
[0139]
[0140]
[0141] The endomorphic density of the artificial aggregate obtained by extrusion-cutting II is 2000~2100kg / m 3 , water absorption rate 0.9.
[0142] Table 9 shows the mix proportion of concrete waste aggregate UHPC shell.
[0143] Table 9 Concrete waste aggregate HPC shell mix ratio (kg / m 3 )
[0144] Silica Fume cement Sand water Water reducing agent UHPC 178 880 900 170 30
[0145] From the above examples, it can be seen that the present invention uses geopolymer (blast furnace slag powder, petroleum coke slag, fly ash) mud-based (saw mud, ultrafine tailings, sand washing mud) solid waste to prepare coarse aggregate, which becomes an effective substitute for natural aggregate, can alleviate the excessive exploitation of natural aggregate, and at the same time realize "waste with solid waste", and realize the efficient organic combination of energy conservation and emission reduction in the building materials industry. Moreover, the present invention will not cause secondary pollution. The waste will directly become the main component of the product during production, and the utilization itself will not produce secondary pollution. It has good social benefits, promotes the disposal of production waste, saves natural resources, and protects the natural environment.
[0146] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. Other embodiments can be obtained based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.
Claims
1. An artificial aggregate endoderm, characterized in that: Including the following raw materials in percentage by weight: Geopolymer 9-40%, mud-based solid waste 45-76%, water 9-20%, water reducer 0.01-6%; The geopolymer includes blast furnace slag powder, desulfurized petroleum coke slag and fly ash; The mud-based solid waste includes ultrafine tailings, saw mud and sand washing mud.
2. The artificial aggregate endometrium according to claim 1, characterized in that: The mass percentages of blast furnace slag powder, desulfurized petroleum coke slag and fly ash in the artificial aggregate endostear are respectively: Blast furnace slag powder 9-20%, desulfurized petroleum coke slag 0.1-10%, fly ash 0.1-10%.
3. The artificial aggregate endometrium according to claim 1, characterized in that: The mass percentages of ultrafine tailings, saw mud and sand washing mud in the artificial aggregate inner embryo are respectively: Ultrafine tailings 25-36%, saw mud 10-20%, sand washing mud 10-20%.
4. The artificial aggregate endometrium according to claim 1, characterized in that: The raw materials for preparing the artificial aggregate endostearum also include a composite activator, which is a mixed solution of water glass and NaOH; The mass of the composite activator is calculated based on the mass of Na2O, and the mass ratio of Na2O in the composite activator to the mass of the geopolymer is (0.03-0.05):
1.
5. The artificial aggregate endometrium according to claim 1 or 2, characterized in that: The mineral composition of the desulfurized petroleum coke slag includes calcium oxide and calcium sulfate; The specific surface area of the blast furnace slag powder is 400-410m 2 / kg, the water hardness coefficient is 1.5-1.74, the alkalinity coefficient is 0.5-0.88, and the activity coefficient is 0.3-0.
46.
6. The artificial aggregate endometrium according to claim 1, characterized in that: The density of artificial aggregate endomorph is 2000~2100kg / m 3 The water absorption rate is 0.5~1%.
7. The method for preparing the artificial aggregate endoderm according to claim 1, characterized in that: The following steps are involved: mixing geopolymer, mud-based solid waste, water and a water reducing agent to obtain an endomorphic slurry; The endoderm slurry is formed and then cured to obtain the artificial aggregate endoderm.
8. An artificial aggregate, characterized in that: It comprises an artificial aggregate endoderm and a cement-based encapsulation shell wrapped on the surface of the artificial aggregate endoderm; the artificial aggregate endoderm is the artificial aggregate endoderm according to any one of claims 1 to 6 or the artificial aggregate endoderm prepared by the preparation method according to claim 7.
9. The method for preparing artificial aggregate according to claim 8, characterized in that: The following steps are involved: Mixing the raw materials for preparing the cement-based encapsulation shell to obtain a cement-based slurry; The artificial aggregate endostearum is immersed in the cement-based slurry for encapsulation to obtain an artificial aggregate semi-finished product; The artificial aggregate semi-finished product is cured to obtain the artificial aggregate.
10. Use of the artificial aggregate according to claim 8 or the artificial aggregate prepared by the preparation method according to claim 9 in building materials.
Citation Information
Cited By
All-solid-waste-based core-shell type carbonized artificial aggregate and preparation method thereof
CN120483600A